2017
DOI: 10.1080/1745039x.2017.1391503
|View full text |Cite
|
Sign up to set email alerts
|

Red beet and betaine as ingredients in diets of rainbow trout (Oncorhynchus mykiss): effects on growth performance, nutrient retention and flesh quality

Abstract: The objective of the study was to evaluate the impact of different concentrations of dietary red beet and betaine on the growth performance and fish flesh quality of rainbow trout. Therefore, a control diet was compared with four diets in which two levels of red beet (14% and 28%) and betaine (0.9% and 1.63%) were incorporated in combination. The study was set up with an average body weight of 69 ± 2.2 g and finished when fish reached commercial weight (175-250 g) after 105 d. The impact of the diets was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Additionally, the increased apparent crude protein digestibility when betaine was supplemented with FM or POS is in line with (El‐Husseiny et al, 2008) and when 0.5% of betaine was dietary supplemented to Nile tilapia, this positive effect of betaine on protein digestibility could be explained by the increase in nutrient absorptive surface (increase villi height) noticed in the current study and increase digestive enzymes as formerly reported by (Wang et al, 2020); however, contrary to our findings is Pinedo‐Gil et al (2017), where they supplemented 0.9 – 1.63% of betaine originated from beetroot to the rainbow trout fish diet and did not notice any effect on apparent nutrient digestibility of crude protein. These interesting results highlight the need for further investigations on the effect of different betaine sources on transcriptional regulation of protein digestibility and amino acid transporters in the gastrointestinal tract of different fish species.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, the increased apparent crude protein digestibility when betaine was supplemented with FM or POS is in line with (El‐Husseiny et al, 2008) and when 0.5% of betaine was dietary supplemented to Nile tilapia, this positive effect of betaine on protein digestibility could be explained by the increase in nutrient absorptive surface (increase villi height) noticed in the current study and increase digestive enzymes as formerly reported by (Wang et al, 2020); however, contrary to our findings is Pinedo‐Gil et al (2017), where they supplemented 0.9 – 1.63% of betaine originated from beetroot to the rainbow trout fish diet and did not notice any effect on apparent nutrient digestibility of crude protein. These interesting results highlight the need for further investigations on the effect of different betaine sources on transcriptional regulation of protein digestibility and amino acid transporters in the gastrointestinal tract of different fish species.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the levels of lipid species are associated with fish quality and nutrient retention. 76 Therefore, these results indicate that we should pay great attention to the impact of environmental pollutants on aquatic organisms.…”
Section: ■ Discussionmentioning
confidence: 92%
“…However, in this report, decreased contents of fatty acids may inhibit the growth performance of zebrafish embryos following propiconazole exposure, showing decreases in hatching rate and body length. Furthermore, the levels of lipid species are associated with fish quality and nutrient retention . Therefore, these results indicate that we should pay great attention to the impact of environmental pollutants on aquatic organisms.…”
Section: Discussionmentioning
confidence: 95%
“…Beta vulgaris did not affect growth, nutritional or biometric parameters as well as nutrient retention compared to the control, while higher red beet had a negative effect on growth and nutritional parameters, which was not agreed with present study results. The Pinedo-Gil et al (2017) results may be partly due to the effect of some antinutritional components in red beet such as tannins or oxalates, which reduce growth and can lead to poor FCR and PER.…”
Section: Pinedo-gil Et Al (2017) Reported That Inclusion Of 14% Red Beetmentioning
confidence: 99%